PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKUTURAL TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.2 SMP NEGERI 4 TAPUNG - Septya Dwi Putri Dwi Putri; Yenita Roza Roza; Nahor Murani Hutapea Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research based on the students’ mathematics achievement at class VIII.2 SMPN 4 Tapung, there are 24 students in the class, only 9 students who achieved the passing grade by the percentage 37,5% on the main discussion about relevancy with teorema pythagoras and then the learning process still teacher center. The research is classroom action research. This aims research to increase learning process and students’ math achievement at class VIII.2 SMPN 4 Tapung through the implentation cooperative learning model of structural Two Stay Two Stray. The subject of the research are 24 students from class VIII.2 SMPN 4 tapung consist of 14 male and 10 famale students with the heterogenous level. Instrument to collect the data are observation and mathematics achivement test. The observation data analyzed by using descriptive and qualitative, and for students’ test by using descriptive and quantitative. The qualitative analysis showed an improvement of learning process prior to action to the first cycle and second cycle. The results of this research showed an increase in students achievement from the based-score with the percentage 29.16%to 45.83% on the first test and 70.83% on the second test. Based on the finding can be concluded that the implentation of cooperative learning model of structural approach Two Stay Two Stray to improve students’ mathematics achievement at class VIII.2 SMPN 4 Tapung in the second semester academic years 2013/2014. Key Word : Students’ Mathematics Achievement, Cooperative Learning Model Structural Approach of Two Stay Two Stray, Classroom Action Research.